Analisis Kebutuhan Tenaga Kependidikan Universitas dalam Melaksanakan Tugas Korespondensi - Yohanes Adven Sarbani; Indriana Lestari (STARKI, 2022)
Correspondence is an important activity in every educational institution. This study aims to analyze the needs of education personnel at Widya Mandala Surabaya Catholic University (UKWMS) in carrying out correspondence tasks. This research approach is quantitative approach with analytical descriptive method. The correspondence at UKWMS was intense. From the data obtained in the questionnaire, on average in a year the letters issued can reach 789 letters, there is even one subsystem that issues 3,000 letters in one year. These letters include invitations, announcements, assignment letters, notifications, reply letters, official notes, and application letters. So far, UKWMS does not have standard guidelines for managing letters that have been approved by the UKWMS leadership. The majority of respondents (86.3%) agree that letter management guidelines are important to support their task in compiling letters. It can be concluded that the existence of correspondence training and letter management guidelines is a necessity for education staff at UKWMS in carrying out correspondence duties Abstrak Korespondensi merupakan aktivitas penting di setiap institusi pendidikan. Penelitian ini bertujuan untuk melakukan analisis kebutuhan tenaga kependidikan Universitas Katolik Widya Mandala Surabaya (UKWMS) dalam pelaksanaan tugas korespondensi. Pendekatan penelitian ini berupa pendekatan kuantitatif dengan metode deskriptif analitis. Korespondensi di UKWMS berlangsung secara intens. Dari data yang didapat di kuesioner, rata-rata dalam setahun surat yang dikeluarkan bisa mencapai 789 surat, bahkan ada satu subsistem yang mengeluarkan 3.000 surat dalam satu tahun. Surat-surat tersebut seperti undangan, pengumuman, surat tugas, pemberitahuan, surat balasan, nota dinas, dan surat permohonan. Selama ini, UKWMS belum memiliki pedoman tata surat yang baku dan disahkan oleh pimpinan UKWMS. Mayoritas responden (86,3%) setuju bahwa pedoman tata surat itu penting untuk mendukung tugas mereka dalam menyusun surat. Bisa disimpulkan bahwa adanya pelatihan korespondensi dan pedoman tata surat merupakan kebutuhan tenaga kependidikan di UKWMS dalam pelaksanaan tugas korespondensi.